Analisis Efektivitas Pembelajaran Daring Selama Pandemi COVID-19 di Madrasah Aliyah - Asep Saepuloh; Dodo (Insanulhaq Cidadungu Foundation, 2024)
The problems faced by madrasas in online teaching and learning activities during the emergency period can be mapped into two things, namely technical and non-technical problems. Technical problems are problems related to technical learning problems. Technical problems are divided into two, namely problems faced by students and problems faced by teachers. This research aims to find out the problems faced by madrasas with the implementation of online learning, while also wanting to find a form of solution implemented by madrasas as a way out of these problems. This research is qualitative research with the research object being Madrasah Aliyah Miftahul Falah Panumbangan Ciamis. The research setting is Madrasah Aliyah Miftahul Falah Panumbangan, with research subjects being teachers and students. The results of this research show that there are a number of problems faced by teachers and students in implementing online learning. This problem is a weakness of online learning compared to face-to-face learning. So the conclusion is that online learning is only an emergency or emergency exit in an educational process. However, during normal conditions, online learning can be a reinforcement of face-to-face learning, so that learning success can be maximized.